Transient flow analysis for pumping system comprising pressure vessel using unsteady friction model - Mehmood, Kashif (2023)
Recent myriad studies on the application of pressure vessels (PVs) to dampen the potentially hazardous transient pressure caused by pump failure are available in the literature. However, little research has been done on integrating these PVs into an instantaneous acceleration-based (IAB) model for transient flow analysis, while most of the reported investigations have been accomplished using the steady-state friction models. Also, scarce literature exists on optimizing the connection configuration of the PV. Nevertheless, unsteady friction (UF) is vital in accurately modeling a transient event, and therefore this study utilizes the IAB UF model to accurately predict the transient response of the pumping pipeline protected by a PV. Based on the proposed numerical model and computational algorithms, a novel approach is also explored to increase the working efficiency of the PV during transient events via a modified connection configuration with the main pipeline. A parametric study has been conducted to determine the impact of the PV's numerous parameters on transient pressure signals. The results reveal that the IAB UF model with two decay parameters can accurately replicate the amplitude and form of transient waves in a pumping system comprising a PV, with almost no deviations between numerical and experimental results. Furthermore, the numerical study shows that the initial air volume, polytropic exponent, installation location, PV size, and connection arrangement of PV with the pump-rising pipeline significantly affect the performance of water hammer protection. However, the flow resistance of connecting pipes containing perforated plates in a separate bypass line reduces the desired vessel volume from the standpoint of economy. The energy-based approach corroborates the use of this design for vessel-to-pipeline connections. The redesigned connection configuration reduces the required volume of PV by up to 70%, which leads to cost-effectiveness.